1981
DOI: 10.1149/1.2127293
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Evolution of Oxygen on Sputtered Iridium Oxide Films

Abstract: We report on the electrocatalytic properties of sputtered iridium oxide films (SIROF's) in acidic electrolytes. Long term stability (240 hr) is demonstrated. Typical steady‐state currents are 75 mA/cm2 at 1.85V (vs. RHE), which is 50% higher than previously reported. In addition, we introduce a new method of determining Tafel slopes based on the short‐time decay of the oxygen evolution reaction (OER) current, corrected for the capacitative component. Tafel plots are presented for samples of different thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

1982
1982
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 1 publication
1
39
0
2
Order By: Relevance
“…However, for the 3Pt3Ir electrodes covered with Nafion used in this work, the H UPD charges are very low which is similar to observations made by Slavcheva et al where diminishing H UPD charges on sputtered electrodes with Pt and Ir oxide with increasing hydration of the Ir oxide layer was seen [29]. Others have shown that especially anodically formed Ir oxide films do not display any H UPD charges [47,50]. No comparison with the H UPD charges was therefore possible to make.…”
Section: Electrochemical Resultssupporting
confidence: 84%
“…However, for the 3Pt3Ir electrodes covered with Nafion used in this work, the H UPD charges are very low which is similar to observations made by Slavcheva et al where diminishing H UPD charges on sputtered electrodes with Pt and Ir oxide with increasing hydration of the Ir oxide layer was seen [29]. Others have shown that especially anodically formed Ir oxide films do not display any H UPD charges [47,50]. No comparison with the H UPD charges was therefore possible to make.…”
Section: Electrochemical Resultssupporting
confidence: 84%
“…63 Frazer and Woods 67 found a higher current density at higher anodic charges, which correlates with the number of potential cycles applied. Hackwood et al 59 compared sputtered with anodically grown IrO 2 films and found higher activity on the sputtered films at small overpotentials, while the performance at high overpotentials was similar. Values of Tafel slopes of sputtered and thermally prepared IrO 2 have already been presented in a review by Matsumoto and Sato, ranging between 40 and 56 mV dec −1 .…”
Section: Single-metal Oxide Electrocatalystsmentioning
confidence: 99%
“…[5][6][7] Iridium-based catalysts have shown good OER catalytic activities 6 and reasonable stability under the highly corrosive anodic potentials and acidic environment required for OER. 8 Unfortunately, iridium is one of the rarest elements in the Earth's crust with an average mass fraction of 0.001 ppm. 1 To make PEM-WEs feasible on a large scale, the amount of Ir required must be signicantly reduced.…”
Section: Introductionmentioning
confidence: 99%